Paleosols of the Interglacial Climates in Canada - Tarnocai, Charles (Géographie physique et Quaternaire, 1990)
ABSTRACTAlthough paleosols are useful indicators of paleoclimates. it is first necessary to establish the relationships between the northern limits of the various contemporary soils and the pertinent climatic parameters. It is then necessary to determine the age of the various paleosols and, if possible, their northern limits. Comparison of the distribution and northern limits of the contemporary soils with the distribution and northern limits of the analogous paleosols then permits the reconstruction of the paleoenvironments. For the purposes of comparison the mean annual temperature of the Old Crow area during the Pliocene epoch was also determined (about 4°C) even though this was not an interglacial period. It was found that during the pre-lllinoian interglacial periods the central Yukon had a mean annual temperature of about 7°C while during the Sangamonian interglacial period it had a mean annual temperature of about - 3°C. During the Holocene epoch, the current interglacial period, the climate has been similar to or only slightly cooler than that existing during the Sangamonian interglacial period. The fluctuating position of the arctic tree line (and associated forest soils) during the Holocene epoch, however, indicates that the climate has also been fluctuating during this time. The paleoclimatic reconstruction presented in this paper also relies heavily on both diagnostic soil features and the soil development during the various interglacial periods.